Prawa pacjenta z perspektywy funkcjonalnej refleksji - Kmieciak, Błażej (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
In 1991 was passed in Poland the Healthcare Institutions Act. In the cited act was for the first time used the phrase of „patient’s rights”. Currently in our country there are several other laws that directly relate to that issue. In recent years, there has also been set up new offices in the field of patients’ rights (Patient Ombudsman, Ombudsman for Psychiatric Patients and specialist for patient’s rights working in hospitals). Discussions concerning rights of the patient most often relate to matters of a formal nature. Specialist literature refers basically to: the issue of consent to treatment, the issue of medical confidentiality, the aspect of the dignity of the patient and the system of protection of patient rights using the services of the health care system. Rarely however – in this context – debates undertake a problem of the importance of interaction between a patient and a doctor. There is also no reflection on the position that physicians and patients occupy in the course of treating. The present text aims to depict the patient’s rights from the perspective of functional reflection. In the first place, it will be presented the context of treatment within which the sick and the doctors as well as nurses play their roles. In particular, it will be shown the commercial face of medical services. Based on the concept of ombudsman will be taken also an attempt to present medical staff as „the first ombudsmen of the rights and interests of the patient.”
Patient’s rights viewed from the functional reflection
Keywords: patient’s rights; functionalism; human rights ombudsman; direct coercion; commercialization of medical services